Pro JSP 2 - Brown, Simon; Dalton, Sam; Li, Sing; Jepp, Daniel; Raible, Matt; Johnson, David (Apress : Imprint: Apress, 2005)
This is the first comprehensive guide to cover JSP 2 and 2.1. It supplies you with the tools and techniques to develop web applications with JSP and Java servlets. You'll learn to choose and implement the best persistence option for your web applications, and how to secure web sites against malicious attack and accidental misuse. You will improve the performance and scalability of JSP pages, as well as architect reliable, stable applications. The authors describe all of the rich JSP 2 features, and explain JSF integration with JSP. Completing the thorough package, this book examines how integration with open source projects like Ant, Struts, XDoclet, JUnit, and Cactus can make web development even easier.